(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article examines the semantic and structural characteristics of synonyms and antonyms in English and Uzbek, focusing on the similarities and differences in their lexical organization, semantic development, and functional usage in both languages. The study highlights that synonyms and antonyms, while universally recognized semantic relations, demonstrate significant language-specific features shaped by cultural, historical, and linguistic factors. In English, synonymy is characterized by a wide range of stylistic shades, etymological diversity, and functional variability due to extensive borrowing and the coexistence of Germanic, Latin, and French lexical layers. In Uzbek, synonymy is strongly influenced by native Turkic roots, historical Persian–Arabic borrowings, and modern socio-cultural developments, which together create a unique system of semantic parallels.